Enhancing flood resilience: a framework for flood risk management system evaluation - Herath, H. M. M.; Amarnath, Giriraj; Alahacoon, Niranga (International Water Management Institute (IWMI), 2024)
Flood risk management faces significant challenges due to its societal, economic, and environmental impacts, which are exacerbated by climate change and its influence on extreme weather events and social dynamics. Recent policies and strategies emphasize flood resilience, shifting from traditional technical approaches to more adaptive, inclusive, and nature-based solutions that address the complex nature of flood risks. Evaluating the impact of flood management projects is essential for assessing their effectiveness in reducing vulnerabilities and enhancing resilience. However, definitions of flood resilience and the effectiveness of strategies remain contested. To address this gap, the research aims to develop a comprehensive framework for systematically evaluating flood resilience, providing guidance for future flood management efforts. The methodology involves conducting a thorough literature review to identify key criteria that link flood risk management, resilience, adaptive capacity, and governance, laying the foundation for the evaluation framework. Flood resilience views floods as opportunities for growth and innovation, fostering more robust, adaptable, and transformative systems that can cope with future uncertainties. Achieving flood resilience requires adaptive and collaborative governance, involving diverse stakeholders such as government agencies, local communities, and the private sector, across multiple scales. The eight parameters for assessing flood resilience focus on key aspects of flood risk governance. These include the capacity to implement diverse management strategies and maintain critical infrastructure, foster multiscale stakeholder collaboration, and involve local communities in decision-making. Other important parameters include flexibility in decision-making, legitimacy through coherent policies, effective risk assessments, resource mobilization, and continuous monitoring and evaluation. Together, these parameters ensure a comprehensive, adaptive, and inclusive approach to managing flood risks and promoting long-term resilience in the face of climate change.